2015
DOI: 10.1007/s00162-015-0364-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative hemodynamics in an aorta with bicuspid and trileaflet valves

Abstract: Bicuspid aortic valve (BAV) is a congenital heart defect that has been associated with serious aortopathies, such as aortic stenosis, aortic regurgitation, infective endocarditis, aortic dissection, calcific aortic valve and dilatation of ascending aorta. There are two main hypotheses to explain the increase prevalence of aortopathies in patients with BAV: the genetic and the hemodynamic. In this study, we seek to investigate the possible role of hemodynamic factors as causes of BAV-associated aortopathy. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…In the present study, the formation and dissipation of vortex rings were observed in all three valve designs during the opening stage. The vortex rings of all the valves were bending towards the flow direction with lobes near the commissures at the early stage of acceleration and separated into small-scale vortices at the acceleration peak, which agrees well with the results from FSI studies on prosthetic aortic valves [37,102]. The vortex distribution in the SPAC molded valve case is similar to that in the case with a conventional valve, and a more complex vortex structure within the valve section was observed in the SPAC tubular valve at the acceleration peak.…”
Section: Vortex Distributionsupporting
confidence: 87%
“…In the present study, the formation and dissipation of vortex rings were observed in all three valve designs during the opening stage. The vortex rings of all the valves were bending towards the flow direction with lobes near the commissures at the early stage of acceleration and separated into small-scale vortices at the acceleration peak, which agrees well with the results from FSI studies on prosthetic aortic valves [37,102]. The vortex distribution in the SPAC molded valve case is similar to that in the case with a conventional valve, and a more complex vortex structure within the valve section was observed in the SPAC tubular valve at the acceleration peak.…”
Section: Vortex Distributionsupporting
confidence: 87%
“…This info from MRI ( Figure 1) was merely used to orient the leaflets in the model correctly. We simulated the trileaflet aortic valve with the common orientation of its leaflets toward the sinuses (RCC, right coronary cusp; LCC, left coronary cusp; and NCC, non-coronary cusp); see [35]. A nonlinear anisotropic May-Newman-Yin model [30] was used to describe the constitute properties of the leaflet tissue.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The valve leaflet models of Griffith and Borazjani suffered from deficiencies; Griffith applied Peskin’s original connected markers; while Borazjani omitted bending stiffness. The CURVIB method was recently extended to include fluid-shell structure interaction by Gilmanov et al ., 57,58 but the efficacy of the approach has not yet been demonstrated for the portion of the cardiac cycle in which the leaflets are coapted and must support large transvalvular pressure differentials. Kamensky et al .…”
Section: Computational Simulationsmentioning
confidence: 99%